ANALISIS MANAJEMEN KINERJA GURU (Studi Kasus Madrasah Aliyah Al Ayyubi di Sidoarjo) - Putri, Rizki Amalia (UNUSA Press, 2017)
Analysis of Performance Management Teacher Madrasah Aliyah Al Ayyubi In Sidoarjo Madrasah Aliyah Al Ayyubi is a private institution located in Sidoarjo East Java. Since 2011 until now, the problem arises that there are indications of not achieving satisfactory performance. This research uses a qualitative approach, which is trying to get as complete information as possible about the performance management of teachers at Madrasah Aliyah Al Ayyubi. Qualitative techniques are used as an approach in this study, because this technique is to understand rational reality as subjective reality especially madrasah citizens to formulate more concrete about teacher performance management. The result is that the existing performance management system in Madrasah Aliyah Al Ayyubi is said to be running almost 60%, in the planning phase Madrasah Aliyah Al Ayyubi has a work program that has been aligned as needed with vision, mission, target and madrasah strategy. However, in its implementation, out of 2 training models defined in the work program, monthly training that includes computer courses and case studies, many of the less participating senior teachers are different from junior teachers who welcome the effort. Another disadvantage of the performance management system in Madrasah Aliyah Al Ayyubi lies in performance evaluation, there is no formal and formal assessment format by Madrasah Aliyah Al Ayyubi and still uses the method of personal discussions and hearings, although previously held daily observations, Weekly and monthly performance of teachers in terms of discipline and teacher competence.